AGAMA DAN BUDAYA MASYARAKAT MADANI - Muh. Anwar HM (State Institute of Islamic Studies (IAIN) Palu, 2006)
This paper discusses Al-Farabi’s concept of civil society and two fundamental ideas that are closely related to it, namely the idea of man as a political animal and the importance of the science of civilization. The paper also deals with Al-Farabi’s philosophy of happiness and explains why religion must serve as the foundation of a civil society. Kata Kunci: Agama, budaya, masyarakat madani